Numerical analysis of blast pressure parameters on the building with and without wall as a barrier - Nur Syafiqah, Abdullah (2019)
Blast loading may result from the detonation of high explosives and chemical ammunitions. There are many blast event occurred near the building that explode either because of terrorism or accidental. This is because the building and infrastructure construct in civilian area are not design to withstand the blast load. Therefore, it is important to consider blast loads in design a building. It is not economical and realistic to design building with full blast resistance. In the event of blast load on building, it will react differently compared to normal load. In this paper, simulation will be done to observe blast pressure profile on building. This research was done to evaluate the blast pressure profile at situation with and without wall. Blast load with 13.6 kg (30 lbs.) Trinitrotoluene (TNT) will be used and will be validated with an article to compare the numerical model 3D with experimental test before it can be used for others parameters. In this numerical analysis, 3 situations will be considered. First, the blast in open space. For the second and third, blast next to the building without and with the presence of RC wall as barrier respectively. The simulation will be done using ANSYS AUTODYN software. From the simulation, it shows that the peak blast overpressure at 18 ft. is almost same with peak blast overpressure of article by Yan et. al (2011). For Yan et. al (2011) the peak blast overpressure is 494.4 kPa at 4.64 msec and peak blast overpressure for free field at 18 ft. is 494.4 kPa at 4.62 msec. For building with the presence of the RC wall blast pressure can be reduce about 120%. The blast peak overpressure at standoff distance 1219 mm (4 ft.) without wall is 1255.63 kPa at 0.22 msec, while the blast peak overpressure with wall is reduced about 315.24 kPa at 1.66 msec at the same standoff distance (1219 mm). The overall result show that with the presence of RC wall, the blast overpressure can be reduced. The numerical result show that RC wall can be used as barrier to reduced blast overpressure.